Deterministic and robust room-temperature exchange coupling in monodomain multiferroic BiFeO3 heterostructures. Issue 1 (December 2017) - Saenrang, W.; Davidson, B.; Maccherozzi, F.; Podkaminer, J.; Irwin, J.; Johnson, R.; Freeland, J.; Íñiguez, J.; Schad, J.; Reierson, K.; Frederick, J.; Vaz, C.; et al.
Abstract Exploiting multiferroic BiFeO3 thin films in spintronic devices requires deterministic and robust control of both internal magnetoelectric coupling in BiFeO3, as well as exchange coupling of its antiferromagnetic order to a ferromagnetic overlayer. Previous reports utilized approaches based on multi-step ferroelectric switching with multiple ferroelectric domains. Because domain walls can be responsible for fatigue, contain localized charges intrinsically or via defects, and present problems for device reproducibility and scaling, an alternative approach using a monodomain magnetoelectric state with single-step switching is desirable. Here we demonstrate room temperature, deterministic and robust, exchange coupling between monodomain BiFeO3 films and Co overlayer that is intrinsic (i.e., not dependent on domain walls). Direct coupling between BiFeO3 antiferromagnetic order and Co magnetization is observed, with ~ 90° in-plane Co moment rotation upon single-step switching that is reproducible for hundreds of cycles. This has important consequences for practical, low power non-volatile magnetoelectric devices utilizing BiFeO3 . Exchange coupling between ferromagnetic and multiferroic materials is a key to magnetoelectric devices but hard to achieve macroscopically. Here, the authors report room–temperature robust and reproducible magnetoelectric switching in Co/BiFeO3 heterostructures with monodomain properties over the entire sample at room temperature.